NOS‐dependent effects of plantar mechanical stimulation on mechanical characteristics and cytoskeletal proteins in rat soleus muscle during hindlimb suspension. Issue 10 (27th September 2021) - Tyganov, Sergey A.; Mochalova, Ekaterina P.; Melnikov, Ivan Y.; Vikhlyantsev, Ivan M.; Ulanova, Anna D.; Sharlo, Kristina A.; Mirzoev, Timur M.; Shenkman, Boris S.
Abstract: The study was aimed at investigating the mechanisms and structures which determine mechanical properties of skeletal muscles under gravitational unloading and plantar mechanical stimulation (PMS). We hypothesized that PMS would increase NO production and prevent an unloading‐induced reduction in skeletal muscle passive stiffness. Wistar rats were hindlimb suspended and subjected to a daily PMS and one group of stimulated animals was also treated with nitric oxide synthase (NOS) inhibitor (L‐NAME). Animals received mechanical stimulation of the feet for 4 h a day throughout 7‐day hindlimb suspension (HS) according to a scheme that mimics the normal walking of the animal. Seven‐day HS led to a significant reduction in soleus muscle weight by 25%. However, PMS did not prevent the atrophic effect induced by HS. Gravitational unloading led to a significant decrease in maximum isometric force and passive stiffness by 38% and 31%, respectively. The use of PMS prevented a decrease in the maximum isometric strength of the soleus muscle. At the same time, the passive stiffness of the soleus in the PMS group significantly exceeded the control values by 40%. L‐NAME (NOS inhibitor) administration attenuated the effect of PMS on passive stiffness and maximum force of the soleus muscle. The content of the studied cytoskeletal proteins (α‐actinin‐2, α‐actinin‐3, desmin, titin, nebulin) decreased after 7‐day HS, but this decrease was successfully prevented by PMS in a NOS‐dependent manner. We also observed significant decreases in mRNA expression levels of α‐actinin‐2, desmin, and titin after HS, which was prevented by PMS. The study also revealed a significant NOS‐dependent effect of PMS on the content of collagen‐1a, but not collagen‐3a. Thus, PMS during mechanical unloading is able to maintain soleus muscle passive tension and force as well as mRNA transcription and protein contents of cytoskeletal proteins in a NOS‐dependent manner.